An analysis of cleaner production planning by applying analytic hierarchy process: a wood industry case study. Issue 3 (4th May 2021) - Hasani Khorshidi, Fatemeh; Azizi, Majid; Ray, Charles; Faezipour, Mohammad Mahdi; Zarea Hosseinabadi, Hamid
ABSTRACT: The production operation plays a crucial role in reducing environmental impacts in various stages of the life cycle of products, from extraction of materials to production, end use, reuse, and recycling. Therefore, the process of reducing these environmental impacts in relation to production contributes to competitive advantage and increased market share. The Medium Density Fibreboard industry consumes high volumes of materials and energy; this study formulates a strategic model for enhancing efficiency and minimising pollution and energy consumption of Medium Density Fibreboard and can be applied to most wood industry production. The Analytical Hierarchy Process was used to analyse the Kimia Choob Golestan medium density fibreboard factory. Reduction of energy consumption (0.228) was identified as the highest priority among the seven cleaner production alternatives. Process change (0.345), planning to prevent unnecessary stoppage in machinery, and equipment use change (0.072) are sub-criteria with highest priority. The results of sensitivity analysis indicate that human resources and process change were the most sensitive factors affecting the rankings.